2022
DOI: 10.1587/elex.19.20220429
|View full text |Cite
|
Sign up to set email alerts
|

6.25-10Gb/s adaptive CTLE with spectrum balancing and loop-unrolled half-rate DFE in TSMC 0.18µm CMOS

Abstract: This paper presents a wide rate range receiver including adaptive continuous time linear equalizer (CTLE) and loop-unrolled half rate decision feedback equalizer (DFE). A hybrid filter is adopted to expand the rate range of adaptive CTLE with spectrum balancing technology. The current-integrating summer is introduced to reduce the power of half-rate loop-unrolled DFE. The post-simulation is carried out by 0.18 μm CMOS TSMC technology and the results show that the rate range of adaptive CTLE can reach to 6.25-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The HF compensation circuit is illustrated on the left, which is a conventional CTLE with capacitive degeneration and inductive peaking techniques. Like a conventional CTLE [9], the high-frequency gainboosting can be tuned by adjusting the control voltages of degeneration resistor and capacitor in the left part. Fig.…”
Section: Ctlementioning
confidence: 99%
See 1 more Smart Citation
“…The HF compensation circuit is illustrated on the left, which is a conventional CTLE with capacitive degeneration and inductive peaking techniques. Like a conventional CTLE [9], the high-frequency gainboosting can be tuned by adjusting the control voltages of degeneration resistor and capacitor in the left part. Fig.…”
Section: Ctlementioning
confidence: 99%
“…Due to the non-ideal effects of channel, it causes significant attenuation of the transmitter data at high frequencies [9,10,11]. [12] adopts a CTLE with adjustable DC gain to compensate the high frequency loss.…”
Section: Introductionmentioning
confidence: 99%
“…In Sun et al (2022), the authors proposed a method to enhance the rate range and reduce power consumption in high-speed serial links by utilizing an adaptive continuous time linear equalizer (CTLE) and a half-rate decision feedback equalizer (DFE) with a hybrid filter and a current-integrating summer. The system was tested using 10 Gb/s PRBS7 signals transmitted through an 18inch FR4 backplane, and the post-simulation results demonstrated a rate range of 6.25-10 Gb/s with excellent performance.…”
Section: High-speed Communication Transmissionmentioning
confidence: 99%
“…The data-traffic explosion driven by cloud computing, 5G networks, industrial IoT, and virtual reality has accelerated the demand for high-speed SerDes transceivers to provide massive data throughput [1,2,3,4,5,6,7,8]. Previous studies have demonstrated that four-level pulse amplitude modulation (PAM-4) is superior to non-return-to-zero (NRZ) for the 56∼112-Gb/s serial data communications due to its doubled spectral efficiency, halved Nyquist frequency, and relaxed clock speeds [9,10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%